Stressors in Multiple Life-Domains and the Risk for Externalizing and Internalizing Behaviors Among African Americans During Emerging Adulthood - Estrada-Martínez, Lorena M. (2012)
Behavioral and mental health outcomes have long been associated with experiencing high levels of stress. Yet, little is known about the link between the nature of stressors, their accumulation over time, and the risk for externalizing and internalizing outcomes. African Americans are exposed to a disproportionate number of stressors beginning earlier in life compared to the general population. Incorporating Agnew’s General Strain Theory into the study of stress, this study examined whether different kinds of stressors are equally salient in the risk for violent behaviors and depressive symptoms among African Americans transitioning into young adulthood. It further examined the effects of the accumulation of stressors in different life domains and their effect on risks. This study utilized data from an African American subsample of an ongoing longitudinal study that followed a panel of 604 adolescents (53% females) from 9(th) grade into adulthood. Multilevel growth curve models were used to examine how changes in four life-domain stressors related to violent behaviors and depressive symptoms. We found that continued exposure to perceived daily stress and racial discrimination stress increased the risk for violent behaviors during young adulthood, and exhibited a nonlinear relationship between the accumulation of stressors and risk for violence. Moreover, we found that exposure to perceived daily stress, financial stress, neighborhood stress, and racial discrimination stress increased the risk of depressive symptoms and led to a linear relationship between the accumulation of stressors and risk for depressive symptoms. Findings suggest identifiable stressors that can persist over time to influence risks at young adulthood.